Peningkatan Keterampilan Sosial Pada Anak Usia Dini Melalui Permainan Tradisional Bengkulu - yanti, dini widiya; sari, rika partika (Universitas Islam Negeri Raden Intan Lampung, 2018)
AbstractThe aims of this research is to get information and data about the effort ti increase children’s social skills in grade B kindergarten through playing method of traditional games in PAUD Yasporbi Kota Bengkulu. Research method used action research method. This method conduced in two cycles according to Kemmis and Taggart model which consist of 4 stages (plan, action, observation and reflection). Data collecting tecniques used field notes, interview, documentation and observation. Research subject was taken from 10 children of 5-6 years old. The result of the research shows that children’s social skills through playing method of traditional games could increase of grade B kindergarten. Analysis of data obtained from the comparison between pre-percentage increase which showed from pre-intervency the class avarage is 47,70% up to 79,79% at posttest result. Keywords: social skills, traditional games.AbstrakTujuan penelitian ini adalah untuk mendapatkan informasi dan data tentang upaya meningkatkan keterampilan sosial melalui permainan tradisional bengkulu di PAUD Yasporbi Kota Bengkulu. Metode penelitian yang dignakan adalah metode Kemmis dan Taggart yang terdiri dari perencanaan, tindakan, observasi dan refeksi. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Subyek penelitian terdiri dari 10 anak berusia 5 -6 tahun. Hasil penelitian ini menunjukkan bahwa keterampilan sosial anak PAUD kelas B melalui metode permainan tradisional sebesar 47,79% dari praintervensi rata-rata kelas dan 79,79% pada hasil posttest.Kata kunci: Keterampilan sosial, permainan tradisonal.